COGNITIVE FUNCTION OF THE ELDERLY IN PALEMBANG CITY NURSING HOMES: AN EPIDEMIOLOGICAL STUDY - Nindela, Rini; Nurusman, Fadilah Aisyah; Suryani, Puji Rizki; Marisdina, Selly; Aini, Syarifah (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
Elderly refers to individuals who have reached the final stage of life, namely 60 years old and above. Physiologically, the elderly will experience various declines in body functions. The decline in cognitive function is among the most common in the elderly. The incidence of cognitive decline in the elderly in Indonesia is relatively high, which is as much as 32.4%, and is most vulnerable at the age of 65 years. Cognitive impairment can cause older adults to have difficulty in doing daily activities (bathing, dressing, washing, cooking), managing finances, getting lost on the road, and other disturbances that make the elderly less independent and confident, then tend to withdraw from social activities. The disturbances can also lead to anxiety disorders and depression. This study aims to determine the profile of cognitive function in the elderly at Palembang Nursing Homes. This cross-sectional study involves all elderly individuals in Palembang City Nursing Homes who meet the inclusion-exclusion criteria. The Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) was used to assess cognitive function. In this study, as many as 69 elderly (87.34%) had experienced a decline in cognitive function. Then, the dominant characteristics in the group that experienced a decrease in cognitive function were >90 years old (100%), women (91.38%), college graduates (100%), never worked (100%), had a history of stroke (92.86%), did not remember or did not know about cognitive impairment history in the family (93.33%). Delayed recall was the aspect that experienced the most disruption (96.2%). This study has revealed that the prevalence of cognitive impairment in Palembang Nursing Homes is exceptionally high. Therefore, it is imperative to implement routine screenings to identify early cognitive impairment in the elderly to provide immediate treatment.